(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2025)
The development of technology in the 4.0 era has changed the global economic environment, especially in terms of financial transaction and consumption behavior. This study aims to examine the impact of digital payments and e-commerce on consumption behavior, with buying habits as a intervening variable, among Islamic economic students (2021-2022) intake. Data collection uses an instrument consisting of a series of questions to be answered by respondents, using a likert scale. The population in this study was 415 students who produces 82 samples using the slovin formula, with a structural equation modeling (SEM) approach based on partial least square (PLS). The results of the study show that digital payments and e-commerce have a significant positive impact on shopping lifestyle. In addition, shopping lifestyle also has a significant positive impact on consumption behavior. However, the direct influence of digital payments and e-commerce on consumption behavior is not significant, indicating that shopping lifestyle acts as a full mediator. This article supports the TPB and TAM theories to explain consumer behavior in the digital era. In practice, digital platform need to provide features that support a shopping lifestyle to reduce consumption behavior.